Use of the Think-Pair Share Type Cooperative Learning Model in Improving Islamic Culture History Learning Outcomes for Class VIII Students at MTs Nurul Falah Ciater, South Tangerang, Banten - Rosfiani, Okta; Fitriani, Silvia; Amraini , Iqra; Lestari, Selvia; Salsabiila, Syifa (PT. Riset Press International, 2024)
This research was motivated by a problem, namely low student learning outcomes, as evidenced by the unsatisfactory learning outcomes of class VIII students at MTs Nurul Falah Ciater, South Tangerang, Banten. Based on this problem, the teacher will apply the Think-Pair-Share Type Cooperative learning model. With this research, researchers hope to improve student learning outcomes. The aim of this research is to determine and improve the learning outcomes of History of Islamic Culture for class VIII students at MTs Nurul Falah Ciater, South Tangerang, Banten using the Think-Pair-Share Type Cooperative Learning Model. The method used in this research was Classroom Action Research (CAR) which was carried out in two cycles. The research instruments used tests, observation sheets and documents. Data was obtained from research subjects, namely 28 Class VIII students at MTs Nurul Falah Ciater, South Tangerang, Banten. The results of this research show that there has been an increase in pre-cycle and cycle 1. The learning outcomes achieved by students in cycle 1 achieved good grades. 79%/22 students have reached and passed the KKTP score of 75. This percentage has exceeded the target of 75% of students who have completed learning and are able to demonstrate about Shalahudin Al Ayyubi Al Adil and Al Kamil. It can be concluded that using the Think-Pair-Share Type Cooperative Learning Model can improve the learning outcomes of class VIII students at MTs Nurul Falah Ciater, South Tangerang, Banten in the subject of History of Islamic Culture.